The Mediating Role Of Strategic Competitive Advantage In Improving Organizational Performance At The Indonesia Air Force Hospital - Budianto, Tri; Arafah, Willy; Anggiani, Sarfilianty (Journal of Comprehensive Science, 2025)
The purpose of this study is to analyze the influence of organizational competence, entrepreneurial orientation, and employee commitment on organizational performance, with strategic competitive advantage as a mediating variable in Indonesian Air Force Hospitals. This research aims to provide empirical insights into the factors contributing to the improvement of hospital performance in the military sector, particularly in addressing competitive challenges and resource constraints. Using a quantitative approach with primary data, the study collected responses from 152 mid-level and senior hospital leaders through a structured questionnaire. The sampling technique employed was non-probability sampling with a purposive sampling method to ensure comprehensive data representation. Data analysis was conducted using Structural Equation Modeling-Partial Least Square with SmartPLS 3.2.9 software. The findings indicate that organizational competence, entrepreneurial orientation, and employee commitment have a positive impact on organizational performance. Additionally, strategic competitive advantage is proven to mediate the influence of organizational competence and entrepreneurial orientation on organizational performance, while the mediation effect of employee commitment was not supported. This study contributes to the theoretical development of strategic management, particularly in organizational behavior and human resource management. Practically, the findings serve as a reference for hospital management in enhancing competitiveness and operational effectiveness through competitive advantage strategies.